GE_GERICHTE P/769/2019 vom 9. September 2019 - GE Cour de justice (2019)
FIXATION DE LA PEINE;EXPULSION(DROIT PÉNAL) | CP.139.al1; CP.1723; CP.139.par22; CP.186; CP.285; CP.286; LEI.115.al1.letb; LEI.115.al1.letc; LStup.19.al1.letc; LStup.19.al1.letd; CP.177.al1; CP.180.al1; LStup.19a.al1